Pelatihan pembuatan minuman probiotik fermentasi dari limbah kulit nanas (Ananas comosus L.) di Desa Seruawan - Kunda, Rony Marsyal; Lokollo, Richard R.; Utami, Prasetyarti; Jesajas, Heryanus; Moniharapon, Mechiavel (INDRA: Jurnal Pengabdian kepada Masyarakat, 2024)
Pineapple skin is an ingredient that can be processed into a probiotic drink. The biggest component of pineapple peel waste besides water is carbohydrates. Pineapple skin can be a good substrate as a source of microbial growth. Pineapple skin can reach 47% of the total fruit and has a chemical composition of 87.80% water, 8.60% sugar and 1.35% reducing sugar. The potential chemical content of pineapple skin has encouraged many researchers to create fermented prebiotic drink products. The ingredients used in making pineapple peel fermented probiotic drinks include: pineapple fruit, fermented yeast, water, palm sugar, cinnamon and granulated sugar. This community service activity was carried out with the aim of educating the public about how to make pineapple peel prebiotic drinks for household scale. There is a need for training in making fermented prebiotic drinks from pineapple peel in local communities. This training will be carried out for the community in Seruawan village, Seram Island, Maluku.